Antibiotic Impact of Certain Hosts on A Polyphagous Pest, Helicoverpa Armigera Hübner Under Ambient Rearing - Yadav, Manish K.; Satapathy, Satya Narayan; Hosamani, Goutam B.; Samal, Basanta Kumar; Patasani, Jitendra; Rout, Dwity Sundar; Nandy, Avisweta (Journal of Advanced Zoology, 2023)
The present study has been designed with the aim to explore the impact of certain established host plants on the biology of polyphagous pest, Helicoverpa armigera Hübner under the ambient rearing. The hosts namely, Tomato (Solanum lycopersicum L), Maize (Zea mays L.), Chickpea (Cicer arietinum L.), Pigeon Pea (Cajanus cajan L.), Mungbean (Vigna radiata L.), and Cotton (Gossypium hirsutum L.) have been used. The test insect, Helicoverpa armigera has been reared under ambient on the mentioned hosts to know the host suitability and further has been evaluated for the bioattributes like feeding index, approximate digestibility (%), pupal weight, growth index and survival index. During investigation, Gram, Cicer arietinum L. [Feeding Index 0.27 ±0.25, Approximate Digestibility per cent 61.40 ±2.14, Pupal Weight (mg) 321.25 ±3.97, Growth Index 0.87 ±0.20 and Survival Index 1.41 ±0.57] followed by Maize, Zea mays L. [Feeding Index 0.21 ±0.3, Approximate Digestibility per cent 57.07 ±3.17, Pupal Weight (mg) 311.34 ±4.31, Growth Index 0.79 ±0.22 and Survival Index 1.37 ±0.54] and Pigeon Pea, Cajanus cajan L. [Feeding Index 0.13 ±0.47, Approximate Digestibility per cent 54.54 ±3.17, Pupal Weight (mg) 297.67 ±2.41, Growth Index 0.61 ±0.31 and Survival Index 1.34 ±0.48] have been found to be the most suitable on the basis of evaluated bioattributes for the development of the test insect, Helicoverpa armigera. It has been recorded that the rest host crops also showed variable performance on different bioattributes of the test insect, Helicoverpa armigera.